Creating a Purgatory of my own: the struggle of keeping it short - Ng, Vanessa Ming Yan (Nanyang Technological University, 2024)
This report documents the progression of the animated short film, “Purgatory”, from start to end. It details the choices made during each stage of the film’s production which affected its look, sound, and script.